Review of Pothiti Hantzaroula, Child Survivors of the Holocaust in Greece: Memory, Testimony and Subjectivity - Mihăilescu, Dana (Historein, 2024)
This article reviews Pothiti Hantzaroula’s Child Survivors of the Holocaust in Greece: Memory, Testimony and Subjectivity (Routledge, 2020). It highlights how Hantzaroula’s book represents a needed and much welcome addition to the study of child survivors of World War II by offering students and scholars of the Holocaust a comprehensive insight into the specifics of Greece, which can serve as a basis for subsequent comparative or kindred assessments in the case of other Southeastern European countries.